Reforms in Indian Banking Sector: Retrospect and Prospect - Agrawal, Mini (IJRDO - Journal of Business Management, 2018)
Why Banking sector reforms were introduced? Banking Sector reforms were introduced mainly to remove the ongoing deficiencies in the banking sector. The reformations in the Indian Banking Sector were brought up with the foundation of the Narasimham Committee which was constituted in 1991. Two reports were submitted by the committee one in 1992 and the other in 1998. The reports basically focused on increasing the efficiency and viability of banking sector. Since before 1991 the banking system was both over regulated and under regulated. Over- regulated in the sense that multiple regulated interest rates were prevailing at that time and a larger proportion of bank funds were restrained from providing loans to private sector for investment by government through high SLR and CRR. And under-regulation in the sense that there was lack of transparency in accounting practices of the banks and non-application of international norms.After nationalization of 14 large banks in 1969, an urgent need of competition aroused in the Indian Money Market which could make the financial system more competitive, productive, and efficient and hence later on Private Banks like HDFC, ICICI banks, UTI banks etc came into existence. Their existence was to bring about “Operational Flexibility” and “Functional Autonomy” in order to improve productivity, efficiency and profitability of banks.